Impact of recipient ACE I/D genotype on kidney function in renal transplant patients: a meta-analysis of cross-sectional and longitudinal studies. (November 2015) - Cargnin, Sarah; Quaglia, Marco; Canonico, Pier Luigi; Stratta, Piero; Terrazzino, Salvatore
Aim: To perform a systematic review and meta-analysis of studies evaluating the influence of recipient angiotensin-converting enzyme insertion/deletion (ACE I/D) polymorphism on kidney function in renal transplant recipients.Materials & methods: A comprehensive search was performed through PubMed, Web of Knowledge and Cochrane databases up to December 2014. The methodological quality of identified studies was assessed using the MINORS criteria.Results: A total of 15 studies evaluating the role of recipient ACE I/D were included in the meta-analysis. In overall analyzes and subsequent subgroup and sensitivity analyzes, no evidence emerged of an effect of ACE I/D on serum creatinine levels, creatinine clearance or glomerular filtration rate.Conclusion: Although further investigation is still needed to determine the role of donor ACE genotype, recipient ACE I/D does not play a significant role on kidney function in renal transplant patients.